2011
DOI: 10.1038/cdd.2011.126
|View full text |Cite
|
Sign up to set email alerts
|

Loss of programmed cell death 4 induces apoptosis by promoting the translation of procaspase-3 mRNA

Abstract: The programmed cell death 4 (Pdcd4), a translation inhibitor, plays an essential role in tumor suppression, but its role in apoptosis remains unclear. Here we show that Pdcd4 is a critical suppressor of apoptosis by inhibiting the translation of procaspase-3 mRNA. Pdcd4 protein decreased more rapidly through microRNA-mediated translational repression following apoptotic stimuli than did the activation of procaspase-3, cleavage of poly(ADP)ribose polymerase (PARP) by active caspase-3, and nuclear fragmentation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 35 publications
1
44
0
2
Order By: Relevance
“…Since PDCD4 inhibits the helicase component of eIF4F, it is likely that PDCD4-sensitive mRNAs might be expected to harbor long and/or highly structured 5′ UTRs. However, to date, very few translational targets of PDCD4 have been identified, with the exception of procaspase-3 [83] and p53 [84] mRNAs.…”
Section: Pdcd4 and Eif4amentioning
confidence: 97%
“…Since PDCD4 inhibits the helicase component of eIF4F, it is likely that PDCD4-sensitive mRNAs might be expected to harbor long and/or highly structured 5′ UTRs. However, to date, very few translational targets of PDCD4 have been identified, with the exception of procaspase-3 [83] and p53 [84] mRNAs.…”
Section: Pdcd4 and Eif4amentioning
confidence: 97%
“…Indeed, research since then has demonstrated that PDCD4 promotes tumor cell apoptosis in hepatocellular, 14 ovarian, 15 glioma, 18 breast 19 and gastric tumor. 20 However, it has been observed that PDCD4 plays an antiapoptotic role in HeLa cells via suppressing proCASP3 mRNA translation 21 and has no impact on apoptosis in colon carcinoma. 7 Furthermore, PDCD4 plays inhibitory functions 22 or no effect 7 on the cell cycle in some tumor cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30] However, recently a study showed that PDCD4 was an antiapoptotic regulator that inhibited the translation of procaspase-3 mRNA in cells. 31 In our study, there was no significant difference in hepatocyte apoptosis between PDCD4-deficient mice and WT mice at 0 h after LPS/D-GalN injection. Therefore, our results indicate PDCD4 deficiency increases the production of proinflammatory cytokines, these cytokines in turn promote hepatocyte apoptosis.…”
Section: Discussionmentioning
confidence: 72%